Effects of Local Watershed Land Use on Water Quality in Mid-Atlantic Coastal Bays and Subestuaries of the Chesapeake Bay - Thomas E. Jordan; Donald E. Weller; Carey E. Pelc (Estuaries and Coasts, 2018)
Nutrient inputs have degraded estuaries worldwide. We investigated the sources and effects of nutrient inputs by comparing water quality at shallow (< 2m deep) nearshore (within 200 m) locations in a total of 49 Chesapeake subestuaries and Mid-Atlantic coastal bays with differing local watershed land use. During July–October, concentrations of total nitrogen (TN), dissolved ammonium, dissolved inorganic N (DIN), and chlorophyll a were positively correlated with the percentages of cropland and developed land in the local watersheds. TN, DIN, and nitrate were positively correlated with the ratio of watershed area to subestuary area. Total phosphorus (TP) and dissolved phosphate increased with cropland but were not affected by developed land. The relationships among N, P, chlorophyll a , and land use suggest N limitation of chlorophyll a production from July–October. We compared our measurements inside the subestuaries to measurements by the Chesapeake Bay Program in adjacent estuarine waters outside the subestuaries. TP and dissolved inorganic P concentrations inside the subestuaries correlated with concentrations outside the subestuaries. However, water quality inside the subestuaries generally differed from that in adjacent estuarine waters. The concentration of nitrate was lower inside the subestuaries, while the concentrations of other forms of N, TP, and chlorophyll a were higher. This suggests that shallow nearshore waters inside the subestuaries import nitrate while exporting other forms of N as well as TP and chlorophyll a . The importance of local land use and the distinct biogeochemistry of shallow waters should be considered in managing coastal systems.